Wear-resistant steel powder, surface modification method of wear-resistant steel powder, feeding and complex part preparation process

Through the design of specific components and surface-modified wear-resistant steel powder, combined with powder injection molding technology, the problem of difficulty in manufacturing complex parts in traditional preparation methods is solved, and wear-resistant steel parts with high strength, toughness and wear resistance are achieved, ensuring high quality and consistency of the product.

CN119876761APending Publication Date: 2025-04-25CHANGZHOU GIAN TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510083960.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional wear-resistant steel preparation methods are difficult to meet the needs of complex parts and micro-complex parts, especially during the sintering process, which faces problems such as narrow sintering window, low sintering density or overfired.

Method used

Using specific component design and surface modification methods of wear-resistant steel powder, the surface of the amino group is grafted through DAMO coupling agent modification treatment, which increases the interaction force between the powder and the binder, and manufactures precision parts of complex shapes through powder injection molding technology.

Benefits of technology

It realizes the high strength, toughness and wear resistance of wear-resistant steel powder, widens the sintering window, improves the sintering density, ensures the high quality and consistency of the product, and is suitable for high-end precision parts manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876761A_ABST
    Figure CN119876761A_ABST
Patent Text Reader

Abstract

The invention relates to wear-resistant steel powder, a surface modification method thereof, feeding and a complex part preparation process. The wear-resistant steel powder comprises the following components in percentage by mass: 1.4-1.5% of C, 4-7% of Cr, 3-5% of Mo, 3-5% of V, less than or equal to 1% of Si, less than or equal to 1% of Mn, less than or equal to 0.03% of S, less than or equal to 0.03% of P, less than or equal to 0.3% of O and the balance of Fe. The preparation process of the complex part comprises the following steps: S1, modifying the surface of wear-resistant steel powder; s2, preparing a wear-resistant steel feed; s3, injection is conducted to obtain an injection blank; s4, degreasing the injection blank to obtain a degreased blank; s5, sintering the degreased blank to obtain a sintered blank; and S6, the sintered blank is subjected to heat treatment, and a final part is obtained. The preparation mode of the wear-resistant steel part is expanded through the powder forming technology, and the powder content ratio is strictly controlled; and meanwhile, the surface of the wear-resistant steel powder is modified, a binder system is optimized, the compatibility of the system is improved by enhancing the interaction of the wear-resistant steel powder and the binder, and the method has an important influence on the field of metal injection molding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder molding, and in particular to wear-resistant steel powder and a surface modification method, feeding and complex parts preparation process thereof. Background Art

[0002] After quenching and tempering, wear-resistant steel forms a fine martensitic matrix with high-hardness metal carbides evenly distributed in the matrix. This treatment method significantly improves the hardness and wear resistance of the material, making it very suitable for parts that require high precision and complex structures, such as hinges for folding screen mobile phones.

[0003] Traditional wear-resistant steel is usually prepared by melting and casting, but this method has limitations in efficiency and product precision. With the improvement of the performance requirements of metal materials in the consumer electronics industry, especially the increase in demand for high strength, toughness and wear resistance, ultra-strong wear-resistant steel has attracted widespread attention due to its excellent material properties. However, traditional preparation methods are difficult to meet the needs of complex parts and micro-complex parts.

[0004] To meet these challenges, powder injection molding has gradually become an effective solution. Although this process performs well in manufacturing micro parts and complex structural parts, the high carbon content of ultra-strong wear-resistant steel faces many problems during sintering, such as narrow sintering window, low sintering density or overburning. Summary of the invention

[0005] The first purpose of the present invention is to provide a wear-resistant steel powder, which has many advantages in performance and embodies significant innovations; at the same time, through modification, the amino groups on the surface of the wear-resistant steel powder can interact with the reactive groups of the binder in the subsequent feeding preparation, and a hydrogen bond or chemical bond is established between the two, thereby improving the compatibility of the entire system and having an important impact on the metal injection molding process.

[0006] The technical solution for achieving the first object of the present invention is: the wear-resistant steel powder in the present invention includes C: 1.4-1.5%, Cr: 4-7%, Mo: 3-5%, V: 3-5%, Si≤1%, Mn≤1%, S≤0.03%, P≤0.03%, O≤0.3%, and the rest is Fe in terms of mass percentage.

[0007] Furthermore, the wear-resistant steel powder is a modified powder body whose surface is grafted with amino groups by modification treatment with a DAMO coupling agent.

[0008] Such a composition design enables the wear-resistant steel powder of the present invention to have multiple advantages in performance and embodies the following significant advantages: High strength and high toughness: The carbon content is between 1.4-1.5%, which makes the alloy have high strength and toughness. Carbon forms carbides with elements such as vanadium and molybdenum, further enhancing the wear resistance and impact resistance of the material. This high strength and high toughness make the wear-resistant steel powder of the present invention particularly suitable for precision parts that need to withstand high loads and strong wear.

[0009] Excellent wear resistance: The chromium content is 4-7%, which significantly improves the wear resistance of the alloy. The carbides formed by the chromium element enhance the material's wear resistance, making it perform well under various working conditions.

[0010] Excellent high temperature performance: The molybdenum content is 3-5%, which enables the alloy to maintain stable mechanical properties under high temperature conditions. Molybdenum improves the strength and heat resistance of steel, and can effectively prevent softening and deformation in high temperature environments, thereby ensuring the service life of the material at high temperatures.

[0011] Enhanced toughness and crack resistance: The vanadium content of 3-5% helps to refine the grain structure of the alloy, enhance toughness and crack resistance. The addition of vanadium improves the comprehensive mechanical properties of the alloy, reduces the occurrence of cracks, and improves the reliability and service life of the material.

[0012] Low content of harmful elements: The content of harmful elements such as silicon (≤1%), manganese (≤1%), sulfur (≤0.03%), phosphorus (≤0.03%) is low, which effectively avoids the adverse effects of these elements on material properties. Low sulfur and low phosphorus content reduces the formation of brittle phases and ensures the toughness and ductility of the alloy.

[0013] Balance of comprehensive properties: By controlling the oxygen content (≤0.3%), the density of the powder during sintering and the mechanical properties of the final product are ensured. The appropriate composition ratio enables the alloy to achieve a good balance between hardness, strength, wear resistance and toughness, showing excellent comprehensive properties.

[0014] Combined with the optimized alloy composition design, the present invention adopts powder injection molding technology, so that precision parts with complex shapes can be manufactured efficiently and accurately. This process not only improves production efficiency, but also significantly reduces production costs, and has important industrial application value. In summary, the wear-resistant steel powder of the present invention shows significant advantages and innovations in composition design and process optimization. Its excellent mechanical properties and wear resistance give it broad application prospects in the field of high-end precision parts manufacturing.

[0015] The second object of the present invention is to provide a surface modification method for wear-resistant steel powder, which uses a DAMO coupling agent to modify the surface of the steel powder and graft amino groups onto its surface, thereby changing the surface properties and chemical activity of the powder. In the subsequent feeding preparation process, the amino groups on the surface of the wear-resistant steel powder can interact with the reactive groups of the binder, thereby enhancing the interaction force between the wear-resistant steel powder and the binder, thereby improving the comprehensive performance of the feeding.

[0016] The technical solution for achieving the second technical purpose of the present invention is: the surface modification method of the above-mentioned wear-resistant steel powder in the present invention comprises the following steps: S1. Weigh the unmodified wear-resistant steel powder, and then weigh 0.25% - 1.25% of the mass of the unmodified wear-resistant steel powder of DAMO silane coupling agent, and add it twice: the first time, after mixing the coupling agent with part of anhydrous ethanol and distilled water, add 40% in a constant temperature water bath when the temperature is raised to 32°C; the second time, when the hydrolysis reaction is carried out for 15 minutes, add the remaining 60%; this design is to quickly form an appropriate amount of active groups in the early stage of hydrolysis to initiate the reaction, and the mid-term supplementation ensures sufficient and uniform hydrolysis, thereby improving the stability and uniformity of the surface modification effect of the wear-resistant steel powder; S2, placing the DAMO silane coupling agent, anhydrous ethanol and distilled water together in a constant temperature water bath at 32°C - 38°C for hydrolysis reaction for 22 - 28 minutes to obtain a coupling agent hydrolysis solution; wherein the molar amount of anhydrous ethanol is 4.2 - 4.8 times that of the DAMO silane coupling agent, and the molar amount of distilled water is 3.2 - 3.8 times that of the DAMO silane coupling agent; S3, put the unmodified wear-resistant steel powder into a mixer, wait for the mixer to heat the unmodified wear-resistant steel powder to 80-120°C, and evenly drop the coupling agent hydrolyzate into the mixer; the mixer mixes at a speed of 700-1000 r / min for 15-45 minutes; after the mixing is completed, take out the powder, wash it repeatedly with anhydrous ethanol, separate the supernatant after standing, and repeat the operation more than three times; S4. Finally, the powder was placed in a blast drying oven at 105°C for 2 hours to obtain a modified powder with amino groups grafted on the surface. This has many advantages in performance and reflects significant innovations. By adopting a specific modification method, amino groups are grafted on the surface of the wear-resistant steel powder. This surface modification changes the surface properties and chemical activity of the powder.

[0017] Preferably, the mass of the DAMO silane coupling agent weighed in step S1 is 0.25% or 0.5% or 0.75% or 1.0% or 1.25% of the mass of the unmodified wear-resistant steel powder.

[0018] In the subsequent feed preparation process, the amino groups on the surface of the wear-resistant steel powder can interact with the reactive groups of the binder, and this process has an important impact on metal injection molding (MIM). On the one hand, the combination based on hydrogen bonds or chemical bonds significantly enhances the interaction between the wear-resistant steel powder and the binder, which greatly improves the compatibility between the two. This high degree of compatibility ensures the uniformity and stability of the feed during the mixing process, effectively avoiding problems such as agglomeration and phase separation caused by poor compatibility between the powder and the binder, thereby ensuring the high quality and consistency of the feed, and laying a solid foundation for the subsequent molding process.

[0019] On the other hand, in the MIM molding process, this strong interaction helps maintain the uniform distribution and precise molding of the feed in the mold cavity. In the injection stage, good compatibility enables the feed to fill the complex cavity of the mold more smoothly, ensuring the dimensional accuracy and shape integrity of the molded parts, and reducing defects caused by uneven fluidity, such as short shots and flash. In the degreasing process, due to the chemical bonding between the powder and the binder, the degreasing process is more gentle and controllable, reducing the internal stress and defects caused by too fast or uneven degreasing rate, and improving the strength and quality of the degreasing blank. In the final sintering stage, the stable powder-binder system can maintain structural stability at high temperatures, which helps to promote the densification and metallurgical bonding between the powder particles, thereby improving the comprehensive properties of the molded parts such as density, hardness and wear resistance, so that the wear-resistant steel parts finally prepared can meet more stringent industrial application requirements, expand its application prospects in aerospace, automobile manufacturing, mechanical processing and other fields, and provide strong material support and technical guarantee for the development of related industries.

[0020] The third object of the present invention is to provide a feed material, wherein the binder improves the bonding property between the wear-resistant steel powder and the binder by optimizing the polymer in the components, thereby improving the feed material compatibility, green body performance and degreasing shape retention, and providing favorable conditions for obtaining high-performance wear-resistant steel complex parts (especially micro parts).

[0021] The technical solution for achieving the second object of the present invention is: the feed material in the present invention comprises the above-mentioned wear-resistant steel powder and binder; wherein the wear-resistant steel powder accounts for 88%-92% of the total mass of the feed material, and the binder accounts for 8%-12% of the total mass.

[0022] The binder comprises 70%-90% of a polyacrylate polymer and 10%-30% of polyethylene glycol by weight; the polyacrylate polymer comprises 20%-40% of a P (MMA-co-HEMA) polymer having a hydroxyl group on the side chain and 60%-80% of a P (MMA-co-GMA) polymer having an epoxy group on the side chain by weight.

[0023] The polyethylene glycol may be PEG1500.

[0024] The composition design of the binder in the above feed has many significant advantages, as described below: Strong binding force with surface modified wear-resistant steel powder: P (MMA - co - HEMA) polymer with hydroxyl group on the side chain and P (MMA - co - GMA) polymer with epoxy group on the side chain work together in the binder system, in which hydroxyl group and epoxy group have high chemical activity. When in contact with the surface modified wear-resistant steel powder, the hydroxyl group can form hydrogen bonds with the amino group on the surface of the powder, and the epoxy group can react chemically with the amino group to form a covalent bond. This multiple interaction mode greatly enhances the binding force between the binder and the wear-resistant steel powder, so that during the molding process, the powder can be evenly and firmly dispersed in the binder system, ensuring the overall stability and consistency of the material, and effectively reducing product defects caused by separation of powder and binder, such as cracks, delamination, etc., thereby improving product quality and reliability.

[0025] Good flexibility and plasticity: Polyethylene glycol (PEG1500) accounts for 10% - 30% of the binder. It has good flexibility and plasticity and can effectively improve the overall rheological properties of the binder. In the metal injection molding process, this makes the feed have better fluidity, can more smoothly fill the complex cavity of the mold, ensure the shape integrity and dimensional accuracy of the molded parts, especially for molds with fine structures or thin-walled parts, good fluidity can avoid defects such as insufficient filling or air holding, and improve the molding efficiency and qualified rate of the product.

[0026] Excellent chemical resistance and stability: Polyacrylate polymers are the main components of the adhesive (70% -90%), which have good chemical resistance and stability. In practical applications, whether it is exposed to chemical reagents during processing or various chemical environments faced during product use, the adhesive can maintain its bonding performance and prevent bonding failure caused by chemical erosion, thereby ensuring the long-term stability and reliability of the product in different chemical environments, extending the service life of the product and broadening its application areas. For example, it can still maintain good performance in industries with corrosive environments such as chemical and marine.

[0027] Synergistic effect: There is a synergistic effect between the components. The relatively high proportion (60% - 80%) of P (MMA - co- GMA) polymers with epoxy groups in the side chains, and the high reactivity of the epoxy groups not only help to combine with the wear-resistant steel powder, but also promote the cross-linking reaction of the entire binder system to a certain extent, and enhance the cohesion and stability of the system; and the appropriate amount of P (MMA - co - HEMA) polymers with hydroxyl groups in the side chains (20% - 40%) further optimizes the compatibility and flexibility of the system through hydrogen bonding, and works together with polyethylene glycol, so that the binder has good bonding properties while taking into account processing performance and performance, providing a strong guarantee for the preparation of high-performance wear-resistant steel-based composite materials.

[0028] The fourth object of the present invention is to provide a process for preparing complex wear-resistant steel parts using the above-mentioned feed material.

[0029] The technical solution for achieving the fourth object of the present invention is: the preparation process of the complex wear-resistant steel parts in the present invention comprises the following steps: S1, preparing the above-mentioned wear-resistant steel powder; S2, prepare above-mentioned feeding; S3, injection: the feed obtained in step S2 is placed in a powder injection molding machine, and injected into a mold cavity at an injection pressure of 110-210 MPa and an injection temperature of 160-210° C. to form an injection blank; S4, catalytic degreasing: the injection blank is subjected to staged catalytic negative pressure degreasing to form a degreased blank; S5, sintering: placing the degreased blank in a monomer sintering furnace to obtain a sintered blank; S6. Heat treatment: heat treat the sintered blank to obtain the final product.

[0030] Furthermore, the surface modification process of the wear-resistant steel powder in step S1 is to use DAMO silane coupling agent to perform surface modification to obtain a modified powder body with amino groups grafted on its surface. Each surface modification of the wear-resistant steel powder adopts the above surface modification method.

[0031] Furthermore, the catalytic degreasing process of step S4 above adopts nitric acid catalytic degreasing, the nitric acid flow rate is 3-6 ml / min, the catalytic temperature is set at 90-130°C, and the degreasing time is t≥(250+70*H)min, where H represents the maximum wall thickness (mm) of the complex part.

[0032] Furthermore, the sintering process of the above step S5 is to carry out sintering in an argon atmosphere, with the sintering temperature controlled at 1150-1250° C. and the heat preservation time being 4-6 hours.

[0033] Furthermore, the heat treatment process of step S6 is as follows: the quenching heat treatment temperature is set at 1050-1150°C, and the high temperature holding time is 2-3 hours; nitrogen cooling is adopted after quenching, and the cooling pressure is set to 8-10 bar, the cooling rate of the first stage is 450°C / min, and the cooling rate of the second stage is 250°C / min. Subsequently, two tempering heat treatments are performed at a temperature of 600-650°C, and each treatment time is 3-5 hours.

[0034] The present invention has positive effects: (1) The present invention expands the preparation method of wear-resistant steel parts through powder molding technology, and strictly controls the proportion of wear-resistant steel powder components; at the same time, the surface of wear-resistant steel powder is modified, and the binder system is optimized. By strengthening the interaction between metal powder and binder, the compatibility of the entire system is improved, and the key preparation problems such as narrow sintering window and low sintering density faced by ultra-strong wear-resistant steel in powder injection molding are effectively solved. In traditional processes, due to the characteristics of wear-resistant steel powder, its sintering temperature range is relatively narrow, and over-burning or under-burning is prone to occur if not careful, resulting in unstable product quality and high scrap rate. However, the present invention, through powder surface modification and optimization of the binder system, enables the powder to achieve sufficient densification within a more suitable temperature range during the sintering process, broadens the sintering window, and improves the sintering density, thereby ensuring the high quality and consistency of the product. These technical improvements have strongly promoted the widespread application of wear-resistant steel in the electronics industry and other fields, and provided more reliable material preparation technology support for the development of related industries.

[0035] (2) The present invention achieves the best performance combination of wear-resistant steel powder by precisely controlling the content of each main component. The synergistic effect of carbon, molybdenum and vanadium significantly improves the wear resistance, strength and high-temperature performance of the alloy. By strictly controlling the content of impurities such as silicon, manganese, sulfur, and phosphorus, the adverse effects of these elements on the performance of the alloy are reduced, ensuring the high purity and high performance of the material. The present invention not only focuses on the improvement of a single performance, but also pays more attention to the balance of comprehensive performance. Through reasonable component design, the corrosion resistance and comprehensive mechanical properties of the alloy are improved, so that the material can perform well in a variety of harsh environments.

[0036] (3) The present invention uses a DAMO coupling agent to modify the surface of the wear-resistant steel powder, so that the powder surface is grafted with amino groups, thereby interacting with the reactive groups of the binder to form a strong hydrogen bond or chemical bond. After the modification, the compatibility and bonding strength between the powder and the binder are significantly improved, and the uniformity and stability during the feeding process are improved. The strength and toughness of the green body are thus enhanced, and the shape can be better maintained during the degreasing and sintering process, reducing the risk of deformation and cracking.

[0037] (4) The present invention improves the bonding between metal powder and binder by optimizing polymer components, thereby improving feed compatibility, green body performance and degreasing shape retention. Polyacrylate polymers and polyethylene glycol (PEG 1500) are used as binders, wherein the polyacrylate polymers include P (MMA-co-HEMA) polymers containing hydroxyl groups on the side chains and P (MMA-co-GMA) polymers containing epoxy groups on the side chains. The hydroxyl-containing P (MMA-co-HEMA) polymer enhances the bonding with metal powder, improves the strength and toughness of the green body, and makes it more stable during subsequent processing. The epoxy-containing P (MMA-co-GMA) polymer further enhances the chemical bonding between the binder and the powder, significantly improving the shape retention of the powder during the degreasing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments and in conjunction with the accompanying drawings, wherein Figure 1 This is a test report diagram of the wear-resistant steel specimen prepared by the present invention after heat treatment; Figure 2 This is a metallographic diagram of the wear-resistant steel specimen prepared by the present invention after heat treatment. DETAILED DESCRIPTION

[0039] (Example 1) The wear-resistant steel powder of the present invention comprises the following components by mass percentage: C: 1.4-1.5%, Cr: 4-7%, Mo: 3-5%, V: 3-5%, Si≤1%, Mn≤1%, S≤0.03%, P≤0.03%, O≤0.3%, and the rest is Fe.

[0040] The feed material in the present invention includes the above-mentioned wear-resistant steel powder and a binder which are uniformly mixed; the binder includes a polyacrylate polymer and a polyethylene glycol (PEG 1500) binder. The specific composition of the binder is as follows:

[0041] The preparation process of the complex wear-resistant steel parts of the present invention comprises the following steps: S1. The wear-resistant steel powder is surface-modified using DAMO silane coupling agent to obtain a modified powder with amino groups grafted on the surface.

[0042] S2. Prepare wear-resistant steel feed: Mix the modified wear-resistant steel powder with the optimized binder in a feed preparation machine to form a uniform feed.

[0043] S3, injection: the wear-resistant steel feed obtained in step S2 is put into a powder injection molding machine, and injected into a mold cavity at an injection pressure of 110-210 MPa and an injection temperature of 160-210° C. to form an injection blank.

[0044] S4. Degreasing: Degreasing is performed on the injection blank to obtain a degreased blank. In this process, nitric acid is used for catalytic degreasing. The nitric acid flow rate is 3-6 ml / min, the catalytic temperature is set at 90-130°C, and the degreasing time is t≥(250+70*H)min, where H represents the maximum wall thickness of the complex parts (mm).

[0045] S5. Sintering: placing the degreased blank in a monomer sintering furnace and sintering it in an argon atmosphere. The sintering temperature is controlled at 1150-1250° C. and the heat preservation time is 4-6 hours to obtain a sintered blank.

[0046] S6, heat treatment: the quenching heat treatment temperature is set at 1050℃, and the high temperature holding time is 2.5 hours; nitrogen cooling is used after quenching, the cooling pressure is set to 8bar, the speed from 1050℃ to 620℃ is 450℃ / min, and the speed from 620℃ to 320℃ is 250℃ / min. Then two tempering heat treatments are carried out, the temperature is 620℃, and the treatment time for each treatment is 3.5 hours.

[0047] S7, Shaping / Machining: The sintered parts are processed according to the standards required by the customer to achieve the best size.

[0048] S8. Other post-processing methods: Surface treatment of parts to improve their performance and durability.

[0049] The test data of the parts prepared in this embodiment are as follows:

[0050] Figure 1 The porosity of the sample after sintering and heat treatment in this example is as low as 0.2%. This result reflects the joint achievements of composition optimization, metal powder surface modification and binder optimization. Composition optimization improves the density and strength of the material and reduces the formation of pores by selecting appropriate metal powder composition and proportion. The surface modification of metal powder introduces amino functional groups, which enhances the bonding force between powders and improves the density during sintering, thereby further reducing the formation of pores. The optimized binder improves the bonding between metal powder and binder, enhances the compatibility and stability of the feed, ensures uniform distribution during injection molding, and avoids the formation of bubbles. The synergistic effect of these three aspects significantly reduces the porosity of the sample and improves its overall performance.

[0051] Figure 2The metallographic diagram further illustrates the influence of these three factors on the material properties. By properly matching carbon and alloying elements, carbides are evenly distributed in the metal matrix, which improves the hardness and wear resistance of the material and enhances its impact resistance. Surface modification and optimized binders promote the refinement and reasonable arrangement of carbides, making the final material perform well in terms of strength and wear resistance.

[0052] (Example 2) The wear-resistant steel powder of the present invention comprises the following components by mass percentage: C: 1.4-1.5%, Cr: 4-7%, Mo: 3-5%, V: 3-5%, Si≤1%, Mn≤1%, S≤0.03%, P≤0.03%, O≤0.3%, and the rest is Fe.

[0053] The wear-resistant steel feed material of the present invention comprises the above-mentioned wear-resistant steel powder and a binder which are uniformly mixed; the binder comprises a polyacrylate polymer and polyethylene glycol (PEG 1500); the specific composition of the binder is as follows:

[0054] The preparation process of the complex wear-resistant steel parts of the present invention comprises the following steps: S1. The wear-resistant steel powder is surface-modified using DAMO silane coupling agent to obtain a modified powder with amino groups grafted on the surface.

[0055] S2. Prepare wear-resistant steel feed: Mix the modified wear-resistant steel powder with the optimized binder in a feed preparation machine to form a uniform feed.

[0056] S3, injection: the wear-resistant steel feed obtained in step S2 is put into a powder injection molding machine, and injected into a mold cavity at an injection pressure of 110-210 MPa and an injection temperature of 160-210° C. to form an injection blank.

[0057] S4. Degreasing: Degreasing is performed on the injection blank to obtain a degreased blank. In this process, nitric acid is used for catalytic degreasing. The nitric acid flow rate is 3-6 ml / min, the catalytic temperature is set at 90-130°C, and the degreasing time is t≥(250+70*H)min, where H represents the maximum wall thickness of the complex parts (mm).

[0058] S5. Sintering: placing the degreased blank in a monomer sintering furnace and sintering it in an argon atmosphere. The sintering temperature is controlled at 1150-1250° C. and the heat preservation time is 4-6 hours to obtain a sintered blank.

[0059] S6, heat treatment: quenching heat treatment temperature is set at 1080℃, high temperature holding time is 3 hours; nitrogen cooling is used after quenching, cooling pressure is set to 8bar, the speed of 1080℃ to 600℃ is 450℃ / min, and the speed of 600℃ to 300℃ is 250℃ / min. Then two tempering heat treatments are carried out, the temperature is 600℃, and the treatment time for each treatment is 3.5 hours.

[0060] S7, Shaping / Machining: The sintered parts are processed according to the customer's requirements to achieve the best size.

[0061] S8. Other post-processing methods: Surface treatment of parts to improve their performance and durability.

[0062] The test data of the parts prepared in this embodiment are as follows:

[0063] (Example 3) The wear-resistant steel powder of the present invention comprises the following components by mass percentage: C: 1.4-1.5%, Cr: 4-7%, Mo: 3-5%, V: 3-5%, Si≤1%, Mn≤1%, S≤0.03%, P≤0.03%, O≤0.3%, and the rest is Fe.

[0064] The wear-resistant steel feed material of the present invention comprises the above-mentioned wear-resistant steel powder and a binder which are uniformly mixed; the binder comprises a polyacrylate polymer and polyethylene glycol (PEG 1500); the specific composition of the binder is as follows:

[0065] The preparation process of the complex wear-resistant steel parts of the present invention comprises the following steps: S1. The wear-resistant steel powder is surface-modified using DAMO silane coupling agent to obtain a modified powder with amino groups grafted on the surface.

[0066] S2. Prepare wear-resistant steel feed: Mix the modified wear-resistant steel powder with the optimized binder in a feed preparation machine to form a uniform feed.

[0067] S3, injection: the wear-resistant steel feed obtained in step S2 is put into a powder injection molding machine, and injected into a mold cavity at an injection pressure of 110-210 MPa and an injection temperature of 160-210° C. to form an injection blank.

[0068] S4. Degreasing: Degreasing is performed on the injection blank to obtain a degreased blank. In this process, nitric acid is used for catalytic degreasing. The nitric acid flow rate is 3-6 ml / min, the catalytic temperature is set at 90-130°C, and the degreasing time is t≥(250+70*H)min, where H represents the maximum wall thickness of the complex parts (mm).

[0069] S5. Sintering: placing the degreased blank in a monomer sintering furnace and sintering it in an argon atmosphere. The sintering temperature is controlled at 1150-1250° C. and the heat preservation time is 4-6 hours to obtain a sintered blank.

[0070] S6, heat treatment: the quenching heat treatment temperature is set to 1100℃, and the high temperature holding time is 2 hours; after quenching, nitrogen cooling is used, the cooling pressure is set to 8bar, the speed from 1100℃ to 580℃ is 450℃ / min, and the speed from 580℃ to 350℃ is 250℃ / min. Then two tempering heat treatments are carried out, the temperature is 580℃, and the treatment time is 3 hours each time.

[0071] S7, Shaping / Machining: The sintered parts are processed according to the standards required by the customer to achieve the best size.

[0072] S8. Other post-processing methods: Surface treatment of parts to improve their performance and durability.

[0073] The test data of the parts prepared in this embodiment are as follows:

[0074] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A wear-resistant steel powder, characterized in that: In terms of mass percentage, it includes C: 1.4-1.5%, Cr: 4-7%, Mo: 3-5%, V: 3-5%, Si≤1%, Mn≤1%, S≤0.03%, P≤0.03%, O≤0.3%, and the rest is Fe.

2. The wear-resistant steel powder according to claim 1, characterized in that: The wear-resistant steel powder is a modified powder body whose surface is grafted with amino groups through modification treatment with a DAMO coupling agent.

3. A surface modification method for the wear-resistant steel powder according to claim 2, characterized in that The following steps are involved: S1. Weigh the unmodified wear-resistant steel powder, and then weigh 0.25% - 1.25% of the mass of the unmodified wear-resistant steel powder. Add DAMO silane coupling agent twice: first, add 40% when the coupling agent is mixed with part of anhydrous ethanol and distilled water in a constant temperature water bath at 32°C; second, add the remaining 60% when the hydrolysis reaction is carried out for 15 minutes; S2, placing the DAMO silane coupling agent, anhydrous ethanol and distilled water together in a constant temperature water bath at 32°C - 38°C for hydrolysis reaction for 22 - 28 minutes to obtain a coupling agent hydrolysis solution; wherein the molar amount of anhydrous ethanol is 4.2 - 4.8 times that of the DAMO silane coupling agent, and the molar amount of distilled water is 3.2 - 3.8 times that of the DAMO silane coupling agent; S3, put the unmodified wear-resistant steel powder into a mixer, wait for the mixer to heat the unmodified wear-resistant steel powder to 80-120°C, and evenly drop the coupling agent hydrolyzate into the mixer; the mixer mixes at a speed of 700-1000 r / min for 15-45 minutes; after the mixing is completed, take out the powder, wash it repeatedly with anhydrous ethanol, separate the supernatant after standing, and repeat the operation more than three times; S4. Finally, the powder was placed in a forced air drying oven at 105° C. for 2 hours to obtain a modified powder with amino groups grafted on the surface.

4. The surface modification method according to claim 3, characterized in that: The mass of the DAMO silane coupling agent weighed in step S1 is 0.25% or 0.5% or 0.75% or 1.0% or 1.25% of the mass of the unmodified wear-resistant steel powder.

5. A feeding method, characterized in that: It comprises the wear-resistant steel powder and binder as described in claim 1 or 2; wherein the wear-resistant steel powder accounts for 88%-92% of the total mass of the feed, and the binder accounts for 8%-12% of the total mass.

6. The feeding method according to claim 5, characterized in that: The binder comprises 70%-90% of a polyacrylate polymer and 10%-30% of polyethylene glycol by weight; wherein the polyacrylate polymer comprises 20%-40% of a P (MMA-co-HEMA) polymer having a hydroxyl group on the side chain and 60%-80% of a P (MMA-co-GMA) polymer having an epoxy group on the side chain by weight.

7. The preparation process of complex wear-resistant steel parts is characterized by The following steps are involved: S1. Prepare the wear-resistant steel powder according to claim 1 or 2; S2. preparing the feed material according to claim 6; S3, injection: the feed obtained in step S2 is placed in a powder injection molding machine, and injected into a mold cavity at an injection pressure of 110-210 MPa and an injection temperature of 160-210° C. to form an injection blank; S4, catalytic degreasing: the injection blank is subjected to staged catalytic negative pressure degreasing to form a degreased blank; S5, sintering: placing the degreased blank in a monomer sintering furnace to obtain a sintered blank; S6. Heat treatment: heat treat the sintered blank to obtain the final product.

8. The process for preparing complex wear-resistant steel parts according to claim 7, characterized in that: The surface modification process of the wear-resistant steel powder in step S1 is to use a DAMO silane coupling agent to perform surface modification to obtain a modified powder body with amino groups grafted on the surface.

9. The process for preparing complex wear-resistant steel parts according to claim 8, characterized in that: Each surface modification step of the wear-resistant steel powder is the surface modification method according to claim 3.

10. The process for preparing complex wear-resistant steel parts according to claim 7, characterized in that: The catalytic degreasing process of step S4 adopts nitric acid catalytic degreasing, the nitric acid flow rate is 3-6 ml / min, the catalytic temperature is set at 90-130° C., and the degreasing time is t≥(250+70*H)min, where H represents the maximum wall thickness (mm) of the complex part.

11. The process for preparing complex wear-resistant steel parts according to claim 7, characterized in that: The sintering process of step S5 is to carry out sintering in an argon atmosphere, control the sintering temperature at 1150-1250° C., and keep the temperature for 4-6 hours.

12. The process for preparing complex wear-resistant steel parts according to claim 7, characterized in that: The heat treatment process of step S6 is as follows: the quenching heat treatment temperature is set at 1050-1150°C, and the high temperature holding time is 2-3 hours; nitrogen cooling is adopted after quenching, and the cooling pressure is set to 8-10 bar, the cooling rate of the first stage is 450°C / min, and the cooling rate of the second stage is 250°C / min. Then, two tempering heat treatments are performed at a temperature of 600-650°C, and each treatment time is 3-5 hours.